2015
DOI: 10.1186/s12904-015-0071-6
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and resource implications of family meetings for hospitalized palliative care patients: research protocol

Abstract: BackgroundPalliative care focuses on supporting patients diagnosed with advanced, incurable disease; it is ‘family centered’, with the patient and their family (the unit of care) being core to all its endeavours. However, approximately 30–50 % of carers experience psychological distress which is typically under recognised and consequently not addressed. Family meetings (FM) are recommended as a means whereby health professionals, together with family carers and patients discuss psychosocial issues and plan car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
0
11
0
5
Order By: Relevance
“…30 It remains unclear whether family meetings, which are resource intensive, have long-term benefits and are cost effective. 31 As services in Australia increasingly move toward fee-for-service or activity-based funding models, such quantification of family meeting outcomes will become increasingly necessary to justify family centered care. 32 Because supporting the quality of life of family members is an explicit component to the World Health Organization definition of palliative care, developing robust evidence for interventions that are designed to support patients and relatives is critical.…”
Section: Discussionmentioning
confidence: 99%
“…30 It remains unclear whether family meetings, which are resource intensive, have long-term benefits and are cost effective. 31 As services in Australia increasingly move toward fee-for-service or activity-based funding models, such quantification of family meeting outcomes will become increasingly necessary to justify family centered care. 32 Because supporting the quality of life of family members is an explicit component to the World Health Organization definition of palliative care, developing robust evidence for interventions that are designed to support patients and relatives is critical.…”
Section: Discussionmentioning
confidence: 99%
“…We also highlight the search for qualification, making it possible, through the studies, to present models / strategies, facilities / difficulties found in providing care to these families and patients. 18 Psychology, however, seems to help in what, for people, is still a taboo: "to prepare for the nearness of death." Fear, anguish, and uncertainty about the unknown are issues specifically attributed to this professional category.…”
Section: Methods Introductionmentioning
confidence: 99%
“…Verificou-se que tais conferências são realizadas como uma estratégia de comunicação, no sentido de prover esclarecimentos acerca do diagnóstico, evolução do quadro e prognóstico, e estabelecer acordos entre equipe e unidade de cuidado em relação aos objetivos do tratamento, além de poder proporcionar suporte psicossocial. Por conseguinte, tal constatação vai ao encontro do que foi explanado na introdução deste estudo (Hudson et al, 2015). Apesar disso, foi identificado que essas reuniões não fazem parte do dia a dia de todos os profissionais, devido à falta de condições de trabalho, outras responsabilidades e à dificuldade de contexto e de habilidade.…”
Section: Compreensão Dos Profissionais Sobre O Papel Da Comunicação Nunclassified